USM AND TOMSK STATE UNIVERSITY TO COLLABORATE IN BIOSCIENCE RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 28 March 2015 – Intensive development in Bioscience will be one of the main areas of focus in an agreement of collaboration between Universiti Sains Malaysia (USM) and Tomsk State University (TSU), Russia.